RHETORICAL FUNCTIONS IN THE INTRODUCTION SECTION OF ENGLISH RESEARCH ARTICLES BY NON-NATIVE SPEAKERS - harno, Su (Faculty of Humanities, Diponegoro University, 2012)
The aims of the study are to examine rhetorical functions in the Introduction, section and to find out whether rhetorical functions employed by non-native speakers have been or have not been conformed to the principles of writing introduction in a research article. The data of this study were collected from a number of science journals written by lecturers of five state universities. As the data belonged to one type of papers, Genre Analysis was employed. The results indicate that majority of the English research articles in the Introduction section by non-native speakers have not met the criteria or principles suggested by the experts representing Anglophone scientific work which has so far still dominated the publication of all scientific information written in English. In order to improve academic writing skill, we should introduce the principles of writing scientific journals to the students of higher education as early possible; let’s say, starting from the first year of study. Keywords: rhetorical functions, genre analysis, research articles, non-nativespeakers